UNCONSTITUTIONALITY OF EC 103/2019 AS TO FIXING THE MINIMUM AGE FOR SPECIAL RETIREMENT: AN APPROACH IN LIGHT OF FUNDAMENTAL LAW TO A BALANCED WORKING ENVIRONMENT/INCONSTITUCIONALIDADE DA EC 103/2019 QUANTO A FIXACAO DE IDADE MINIMA PARA A APOSENTADORIA ESPECIAL: UMA ABORDAGEM A LUZ DO DIREITO FUNDAMENTAL AO MEIO AMBIENTE DE TRABALHO EQUILIBRADO - Serafin, Gabriela Pietsch; Reupke, Erika Giovanini; Jacobsen, Gilson (Revista eletrônica direito e política, 2021)
This paper presents a reflection on the right to special retirement and the establishment of a minimum age for its enjoyment by Constitutional Amendment 103/2019. The approach to the theme explores the Welfare State, human dignity and social protection, walking for the fundamental right to a balanced work environment and special retirement, a social security benefit that seeks to reduce the time of inactivation to protect the health and life of the worker covered with social benefits subject to harmful agents in his/her work. It analyzes the constitutionality of setting a minimum age for special retirement with regard to health and life protection. Research, data processing and reporting are conducted on the basis of the inductive method. KEYWORDS: Social Law. Social Security Law. Special Retirement. Constitutional Amendment 103/2019. Constitutionality. Este trabalho apresenta uma reflexao acerca do direito a aposentadoria especial e da fixacao de idade minima a sua fruicao pela Emenda Constitucional 103/2019. A abordagem do tema explora o Estado Social, a dignidade humana e protecao social, trilhando pelo direito fundamental ao ambiente de trabalho equilibrado e a aposentadoria especial, beneficio previdenciario que busca, na reducao de tempo a inativacao, a protecao da saude e da vida do trabalhador-segurado sujeito a agentes nocivos em seu labor. Analisa a constitucionalidade da fixacao de idade minima a aposentadoria especial no que toca a protecao da saude e da vida. A investigacao, o tratamento dos dados e a elaboracao do relato desta pesquisa sao realizados com base no metodo indutivo. PALAVRAS-CHAVE: Direito Social. Direito Previdenciario. Aposentadoria Especial. Emenda Constitucional 103/2019. Constitucionalidade.